ChemInform Abstract: Direct Cross‐Coupling Access to Diverse Aromatic Sulfide: Palladium‐Catalyzed Double C—S Bond Construction Using Na2S2O3 as a Sulfurating Reagent. Issue 32 (24th July 2014) - Qiao, Zongjun; Wei, Jianpeng; Jiang, Xuefeng
Abstract: Aromatic thioethers are efficiently synthesized by cross‐coupling of (het)aryl halides with alkyl chlorides in the presence of odorless and stable solid sodium thiosulfate.